Solutions to Improve Welfare in Indonesia: Agency Theory Perspective - Khairudin Khairudin; Aminah Aminah; Riswan Riswan (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2026)
This study focuses on testing the effect of good governance on welfare moderated by corruption in all provincial governments in Indonesia during the period 2014-2018. The test was conducted using panel data regression, where welfare was measured using the human development index value, good governance was measured using the governance index based on the principles of good governance from KNKG which was processed using the Principal Component Analysis method, corruption was measured using the number of irregularities found by government audit institutions, and the size of the regional government was measured using the number of state civil servants. The research data came from BPK-RI and BPS-RI. The test results found that good governance had a positive and significant effect on welfare, and corruption weakened the relationship between good governance and welfare, so the implementation of good governance and the continuous eradication of corruption in regional government organizations is very important.